2001
DOI: 10.1007/s004380100531
|View full text |Cite
|
Sign up to set email alerts
|

DDT resistance in Drosophila correlates with Cyp6g1 over-expression and confers cross-resistance to the neonicotinoid imidacloprid

Abstract: Mutagenesis can be used as a means of predicting likely mechanisms of resistance to novel classes of insecticides. We used chemical mutagenesis in Drosophila to screen for mutants that had become resistant to imidacloprid, a neonicotinoid insecticide. Here we report the isolation of two new dominant imidacloprid-resistant mutants. By recombinational mapping we show that these map to the same location as Rst(2)DDT. Furthermore, we show that pre-existing Rst(2)DDT alleles in turn confer cross-resistance to imida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
232
1
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(247 citation statements)
references
References 14 publications
12
232
1
2
Order By: Relevance
“…4). As expected (12,33), all Accord insertion lines had substantially higher levels of Cyp6g1 transcript. These data are consistent with the hypothesis that both the D. simulans Doc insertion and the D. melanogaster Accord insertion cause constitutive Cyp6g1 up-regulation.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…4). As expected (12,33), all Accord insertion lines had substantially higher levels of Cyp6g1 transcript. These data are consistent with the hypothesis that both the D. simulans Doc insertion and the D. melanogaster Accord insertion cause constitutive Cyp6g1 up-regulation.…”
Section: Resultssupporting
confidence: 77%
“…The Accord insertion occurs Ϸ300 bp upstream of the transcription start site (1. (12,33), suggesting that mutations increasing transcript abundance of Cyp6g1 might be favored in certain environments. We compared Cyp6g1 mRNA transcript levels in adult flies from Californian D. simulans lines homozygous for the Doc insertion (n ϭ 3) and African D. simulans lines homozygous for absence of the insertion (n ϭ 3) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In early genetic studies in Drosophila, dichlorodiphenyltrichloroethane (DDT) resistance was mapped to multiple locations on chromosomes II and III (8)(9)(10)(11)(12)(13)(14)). Subsequently, low-level DDT resistance was mapped to 64.5 Ϯ 2 centiMorgans on the second chromosome (15), a locus (loci) known as Rst (2)DDT.…”
mentioning
confidence: 99%
“…However, it has been shown that TE insertions in the proximity of Cyps can alter their regulation and cause the over-expression of CYP enzymes, resulting in insecticide resistance (Catania et al, 2004;Daborn et al, 2001Daborn et al, , 2002Jouben et al, 2008). TE insertions could therefore also be a source of genetic variability, and the regulatory motifs they provide could be advantageous for organisms in responding to external stimuli.…”
Section: Discussionmentioning
confidence: 99%